Maracun: Pengatahuan Petani Sayur Dalam Penggunaan Pestisida di Dataran Tinggi Kabupaten Solok - Mustika Illahi (Balale' : Jurnal Antropologi, 2022)
The use of pesticides is one way of getting rid of pests for farmers, because pesticides provide quick benefits for farmers' crops. If the plant is exposed to pests, the pesticide is directly applied to the plant. Apparently, at this time the use of pesticides is not only as a pest control. There are other uses, namely as plant guards to avoid pests and diseases. So that the intensity of pesticide application on vegetable crops is increasing.This study uses a descriptive qualitative research method. The data collection techniques using observation, interviews, documentation and literature study. For the selection of informants using a purposive technique where the informants are selected according to the specified criteria. The data obtained is then analyzed by selecting the data obtained and categorized based on the existing categories. Then the author divides the informants into two categories, namely key informants and regular informants.The results showed that pesticides are still used by farmers because they are still one of the killers of pests and also the way to obtain pesticides is very easy. The application of pesticides is carried out by mixing at least 5 types of pesticides in one spray. The knowledge gained by farmers in the use of pesticides comes from the farmers' personal experiences and also learns from farm stall keepers, pesticide product salespeople and from fellow farmers.